2016
DOI: 10.1136/oemed-2015-103342
|View full text |Cite
|
Sign up to set email alerts
|

Night shift work and incidence of diabetes in the Danish Nurse Cohort

Abstract: Danish nurses working night and evening shifts have increased risk for diabetes, with the highest risk associated with current night shift work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
95
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 36 publications
2
95
1
4
Order By: Relevance
“…Another study showed that the evening chronotype was risk of diabetes and metabolic syndromes [16]. In fact, it is well known that night shift work is a risk of incident diabetes [17,18]. Thus, dinner timing is an important issue in the clinical setting.…”
mentioning
confidence: 99%
“…Another study showed that the evening chronotype was risk of diabetes and metabolic syndromes [16]. In fact, it is well known that night shift work is a risk of incident diabetes [17,18]. Thus, dinner timing is an important issue in the clinical setting.…”
mentioning
confidence: 99%
“…Observational studies suggest an association between shift work and various health problems, including circadian dysrhythmia, fatigue and insufficient recovery,1 2 breast cancer,3 cardiovascular disorders4 and type-II diabetes 5. Survey studies on shift work and health are sensitive for exposure misclassification 2 6.…”
Section: Introductionmentioning
confidence: 99%
“…Shift work has been associated with increased prevalence for obesity, diabetes, systemic inflammation, and other metabolic comorbidities. [78][79][80][81][82][83][84][85] Human participants exposed to a forced desynchrony protocol display hyperglycemia, insulin resistance, poor glucose tolerance, increased arterial pressure, and reversed cortisol rhythms when they are ~12 hours out of phase with the environmental light-dark cycle. 86 The 12-hour phase shifts also increase blood pressure, C-reactive protein, and inflammatory mediators and decrease vagal tone, …”
Section: Circadian Desynchronymentioning
confidence: 99%